Potential applications of nanotechnology in bioenergy - Kramb, Jason (2011)
Nanotechnology has an increasingly large impact on a wide range of industries, but its current use in the production of electricity and heat from biomass is limited. This thesis examined the potential impact of nanotechnology on bioenergy production through a literature review and interviews with industry members. Current technologies and methods in use were reviewed, with a focus on fuel handling and combustion systems. Areas in which problems existed were identified and nanotechnologies with properties relevant to those problems examined. The major nanotechnology areas which were reviewed are nanostructured coatings (wear resistant, corrosion resistant, low friction and anti-icing), nanomembranes for gas separation, nanostructured catalysts for emission reductions, thermoelectrics and thermophotovoltaics. Basic economic analyses were also performed to determine conditions for economic viability of the nanotechnology solutions. The thesis concludes that while there are many areas which have promising technologies in development, there are no clear nanotechnology solutions which can be implemented cost effectively at the current time. Recommendations for future work are also made.